Analyzing the Role of Government Support in Moderating Behavior and Revisit Intention in Halal Tourism - Karya, Denis Fidita; Ratnasari, Vita; Anshori, Mohamad Yusak (Journal of Ecohumanism, 2025)
In the current era of globalization, the tourism industry faces demands to continue to adapt to changing tourist preferences, including for those who follow halal lifestyles and principles. The phenomenon of halal tourism is growing, demanding a deeper understanding of the factors that influence the behavior of Muslim travelers in choosing destinations and contributing to the sustainability of halal destinations. This study aims to investigate the impact of Halal Literacy, Perceived Risk, and Perceived Uncertainty on the Theory of Planned Behavior (SDGs) and how their influence influences the behavior and intention to return Muslim travelers, with Government Support as a moderator variable. This research is quantitative. Data was collected using a purposive random sampling method by distributing a questionnaire to 200 tourists visiting halal destinations in East Java. The results of this study explain that all hypotheses have a significant positive influence, except subjective norms, on behavior. In addition, using government support as moderator has a significant positive effect on behavior and revisit intention.